Numerical Study on Crack Propagation by Using Softening Model under Blasting. (2nd August 2015) - Hu, Rong; Zhu, Zheming; Xie, Jun; Xiao, Dingjun
Abstract : A mixed failure criterion, which combined the modified maximum principal stress criterion with the damage model of tensile crack softening, was developed to simulate crack propagation of rock under blasting loads. In order to validate the proposed model, a set of blasting models with a crack and a borehole with different incident angles with the crack were established. By using this model, the property of crack propagation was investigated. The linear equation of state (EOS) was used for rock, and the JWL EOS was applied to the explosive. In order to validate the numerical simulation results, experiments by using PMMA (polymethyl methacrylate) with a crack and a borehole were carried out. The charge structure and incident angle of the blasting experimental model were the same as those in the numerical models. The experiment results agree with the numerical simulation results.